2023
DOI: 10.1111/sms.14367
|View full text |Cite
|
Sign up to set email alerts
|

Fractional exhaled nitric oxide in the assessment of exercise‐induced bronchoconstriction: A multicenter retrospective analysis of UK‐based athletes

Abstract: Introduction Exercise‐induced bronchoconstriction (EIB) is not only highly prevalent in people with asthma, but can also occur independently, particularly in athletes. Fractional exhaled nitric oxide (FeNO) is an indirect biomarker of type 2 airway inflammation that has an established role in the assessment and management of asthma. The aim was to evaluate the value of FeNO in the assessment of EIB in athletes. Method Multicenter retrospective analysis. In total, 488 athletes (male: 76%) performed baseline FeN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The ERS recommends a cutoff of >50 ppb for a specificity of >90% or a cutoff of >40 ppb for the best compromise between sensitivity and specificity. In support of this, Dickinson et al (16) have reported a study involving recreational and elite athletes from a wide range of athletic disciplines, that F ENO ≥ 40 ppb predicts EIB with the best specificity/sensitivity ratio (86% and 37%, respectively). However, given the low sensitivity, the authors recommend against using F ENO alone in diagnosing EIB.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The ERS recommends a cutoff of >50 ppb for a specificity of >90% or a cutoff of >40 ppb for the best compromise between sensitivity and specificity. In support of this, Dickinson et al (16) have reported a study involving recreational and elite athletes from a wide range of athletic disciplines, that F ENO ≥ 40 ppb predicts EIB with the best specificity/sensitivity ratio (86% and 37%, respectively). However, given the low sensitivity, the authors recommend against using F ENO alone in diagnosing EIB.…”
Section: Discussionmentioning
confidence: 84%
“…Elevated fractional exhaled nitric oxide (F ENO ) is a marker of airway eosinophilic inflammation and a recommended diagnostic tool for bronchial asthma in the normal population (14,15). However, F ENO levels in athletes may be different than of the general population, as highlighted by a recent study where 45% of the participants with EIB had values <25 ppb (16).…”
mentioning
confidence: 99%
“…A recent multi-center retrospective analysis involving 488 athletes has shown that an FeNO level of ≥40 ppb offers good specificity, allowing it to be useful in confirming a diagnosis of EIB. However, given its limitations in sensitivity and predictive values, FeNO should not be used as a substitute for indirect bronchial provocation testing in athletes [ 45 ].…”
Section: Diagnosis Of Eia In Athletesmentioning
confidence: 99%